2006
DOI: 10.1007/s10555-006-8500-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of metastasis

Abstract: A major topic covered at the First International Symposium on Cancer Metastasis and the Lymphovascular System was the molecular mechanisms of metastasis. This has become of major interest in recent years as we have discovered new metastasis-related genes and gained understanding of the molecular events of lymphatic metastasis. The symposium covered new aspects and important questions related to the events of metastasis in both humans and animals. The basic and clinical related research covered in this topic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 151 publications
0
37
0
Order By: Relevance
“…The chemokine CXCL12 is supposed to be involved in lymphogenesis via its receptor CXCR4 and CCL21 mediates homing of lymphocytes and migration of dendritic cells into lymphatic vessel. Nonetheless, it has been reported that chemokines and their receptors are expressed in a variety of human cancers such as melanoma, breast cancer, gastric cancer or prostate cancer (Hoon, Kitago et al 2006). Recent findings about the direct role of chemokines in LNM in CRC, suggested an involvement of CXCR3, CXCL12/CXCR4 and CCL21/CCR7 (Kawada and Taketo 2011;Singh et al 2011;Raman et al 2010).…”
Section: Chemokinesmentioning
confidence: 99%
“…The chemokine CXCL12 is supposed to be involved in lymphogenesis via its receptor CXCR4 and CCL21 mediates homing of lymphocytes and migration of dendritic cells into lymphatic vessel. Nonetheless, it has been reported that chemokines and their receptors are expressed in a variety of human cancers such as melanoma, breast cancer, gastric cancer or prostate cancer (Hoon, Kitago et al 2006). Recent findings about the direct role of chemokines in LNM in CRC, suggested an involvement of CXCR3, CXCL12/CXCR4 and CCL21/CCR7 (Kawada and Taketo 2011;Singh et al 2011;Raman et al 2010).…”
Section: Chemokinesmentioning
confidence: 99%
“…To determine population doubling time of adherent cultures, 5x10 5 viable cells were seeded in 25-cm 2 flasks, and growth curves were obtained by a direct count of cells harvested with trypsin-EDTA for 5 days after seeding. For anchorage-dependent clonogenicity, 200-6,400 cells were seeded in 60-mm tissue culture Petri dishes in DMEM + 20% FBS.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…Experimental models to evaluate the role played by candidate molecules in the metastatic process can take advantage of gene engineering to modify gene expression on the one hand (4), and several methods to induce metastasis on the other, for example the direct intravenous injection of cells that simulate the late, post-intravasation phases of metastasis (5).…”
Section: Introductionmentioning
confidence: 99%
“…Although melanoma is an aggressive type of skin cancer that carries significant morbidity and mortality, the prognosis for patients with localized tumor is quite good, the aggravation being the metastatic capacity of the tumor. When the process of metastasis takes place, the prognosis is generally very poor, with the metastatic melanoma being rarely curable [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Because of that, there is still a lot unclear understanding about the progression of the disease, making it difficult to ensure which molecular pathways are involved in each step of the disease development. Therefore, for the development of new prognostic and therapeutic targets of melanoma metastasis, it is important to elucidate which pathways are involved specifically in the progression of the localized tumor to its metastasis [2]. For that, a deep review of the literature, analysing carefully which pathologic classification each study considered, may clarify the molecular alterations involved specifically in the most aggressive step in melanoma progression.…”
Section: Introductionmentioning
confidence: 99%